Predictors of Conviction: An Examination of Arson Trial Outcomes in Florida - York, Timothy (2018)
The influences that crime control, due process factors, and individual demographic characteristics have on the criminal trial outcomes of accused arsonists was unknown. Absent this knowledge, it was not clear if public policy ensures justice for the accused, particularly for the disadvantaged. The purpose of this quasi-experimental study was to investigate, using Packer's due process and crime control model as the theoretical framework, the relationship between time to trial, number of defense and prosecution witnesses, access to fire origin and cause experts, legal representation type, age, race, education, and gender and criminal arson case outcomes. A sample size of 165 archival court records of those accused of arson from 2011-2015 were analyzed using Packer. According to the results of the logistic regression models, there was a significant relationship (p < .05) between trial outcomes and the use of fact witnesses by the defense and by the prosecution.This relationship moved the pendulum toward crime control for the selected population. The ordered logistic model explained 6.9% of the variation in the criminal case outcomes. Policymakers can use the results of this study to inform criminal justice policy and to prioritize funding to assure fairness and social justice for the accused. Arson defendants and their counsel can use the results to prepare their defense to assure their social justice while prosecutors can use the results to better inform their decisions to assure the legal and factual guilt of the defendant. Future research is needed to provide a clearer understanding of the role that other variables play in the outcome for the population